PRAKTEK JUAL BELI DI PASAR TRADISIONAL DESA PANDAHAN KECAMATAN BATI-BATI DALAM PERSFEKTIF EKONOMI ISLAM - Anwar, Mukhlis Kaspul (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This research was motivated by the existence of a traditional market in Pandahan Village, Bati-bati District, which is a traditional market with an Islamic nuanced system. Therefore, this study aims to find out how the practice of buying and selling practices of traditional markets in Pandahan Village, Bati-bati District, from an Islamic economic perspective. This type of research is field research conducted with qualitative assessment. The location of the study is at the Traditional Market of Pandahan Village which is located at Jl. A. Yani km 28 RT 04 Pandahan Village, Bati-bati District, Tanah Laut Regency, Kalimantan Province, South Kalimantan. The results showed that , the traders of the traditional market of Pandahan Village, Bati-bati District apply the practice of buying and selling with a perfect contract system, the right to vote (khiyar), voluntary, without containing elements of coercion, bringing benefits and avoiding mudharat in society, avoiding garar, avoiding riba